The floral nectary of Hymenaea stigonocarpa (Fabaceae, caesalpinioideae): Structural aspects during floral development - Paiva, Elder Antonio Sousa; Machado, Silvia Rodrigues [UNESP] (Oxford University Press, 2008)
Background and Aims Considering that few studies on nectary anatomy and ultrastructure are available for chiropterophilous flowers and the importance of Hymenaea stigonocarpa in natural 'cerrado' communities, the present study sought to analyse the structure and cellular modifications that take place within its nectaries during the different stages of floral development, with special emphasis on plastid dynamics.Methods For the structural and ultrastructural studies the nectary was processed as per usual techniques and studied under light, scanning and transmission electron microscopy. Histochemical tests were employed to identify the main metabolites on nectary tissue and secretion samples.Key Results The floral nectary consists of the inner epidermis of the hypanthium and vascularized parenchyma. Some evidence indicates that the nectar release occurs via the stomata. The high populations of mitochondria, and their juxtaposition with amyloplasts, seem to be related to energy needs for starch hydrolysis. Among the alterations observed during the secretory phase, the reduction in the plastid stromatic density and starch grain size are highlighted. When the secretory stage begins, the plastid envelope disappears and a new membrane is formed, enclosing this region and giving rise to new vacuoles. After the secretory stage, cellular structures named 'extrastomatic bodies' were observed and seem to be related to the nectar resorption.Conclusions Starch hydrolysis contributes to nectar formation, in addition to the photosynthates derived directly from the phloem. In these nectaries, the secretion is an energy-requiring process. During the secretion stage, some plastids show starch grain hydrolysis and membrane rupture, and it was observed that the region previously occupied by this organelle continued to be reasonably well defined, and gave rise to new vacuoles. The extrastomatic bodies appear to be related to the resorption of uncollected nectar.
Keywords: cell ultrastructure; cerrado vegetation; extrastomatic bodies; Fabaceae; floral nectary; Hymenaea stigonocarpa; nectar; plastids; secretion; starch hydrolysis; vacuole